2014
DOI: 10.15200/winn.141832.26907
|View full text |Cite
|
Sign up to set email alerts
|

The rising trend in authorship

Abstract: Big science is on the rise. Recent endeavors, such as the Large Hadron Collider and the Human Genome Project, illustrate the rise in large-scale scientific inquiries. To assess whether big science is part of a general trend towards increased authorship, we queried the publicly available database Pubmed and measured the trend in number of authors per paper over the last century. Here we show that authorship has increased five-fold since 1913 and predict that by 2034, publications will boast an average of 8 auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 2 publications
3
35
0
Order By: Relevance
“…Histogram of number of authors in the PLoS ONE dataset reveals a irregular distribution: most of the papers includes the collaboration of 2-9 authors. Interestingly, we also observe a significant number of papers including more than 10 authors, which is in accordance with recent reported trends [27]. To investigate how individuals contributions varies in papers, we used the effective number of authors (N ) as a measure of variability, as defined in Section II B.…”
Section: Resultssupporting
confidence: 88%
“…Histogram of number of authors in the PLoS ONE dataset reveals a irregular distribution: most of the papers includes the collaboration of 2-9 authors. Interestingly, we also observe a significant number of papers including more than 10 authors, which is in accordance with recent reported trends [27]. To investigate how individuals contributions varies in papers, we used the effective number of authors (N ) as a measure of variability, as defined in Section II B.…”
Section: Resultssupporting
confidence: 88%
“…We set these thresholds in the context of a large‐scale study (>20 million papers) of authorship in scientific papers (Aboukhalil ). As defined here, sole authors, small teams, and large teams are recognizable in the histogram of author numbers presented by Aboukhalil (). We ran all time‐to‐event analyses with the R packages survival (Therneau & Grambsch ; Therneau ) and survminer (Kassambara & Kosinski ).…”
Section: Methodsmentioning
confidence: 99%
“…Here often people turn to the average number of authors as a measure (e.g. Aboukhalil 2014). While this is a useful statistics, it is heavily biased towards the few papers with an extreme number of authors.…”
Section: Data Processingmentioning
confidence: 99%